Comparison of the efficacy of expandable interbody fusion cage (EXP-IFC) and non-expandable interbody fusion cage (NE-IFC) in MIS-TLIF for lumbar degenerative diseases: A systematic retrospective study on 62 patients - Chen, Chen; Li, Qiang; Wang, Wei; Ji, Chunlei; Kang, Yi; Wang, Chaoyu; Zhang, Hongyi; Zhang, Ming; Zhou, Hengxing; Feng, Haoyu; Feng, Shiqing (Frontiers in Surgery, 2022)
Objectives: To investigate the clinical and radiographic outcomes of EXP-IFC in single-level MIS-TLIF. Methods: Patients ≥18 years of age who underwent single-level MIS-TLIF with minimum 1 year follow-up were included. Outcome measures: clinical features, preoperative and neurological complications. Imaging analysis included disc height (DH) restoration, surgical and contralateral side foraminal height (FH), lumbar lordosis angle (LL), segmental lordosis(SL). Clinical outcomes were evaluated using visual analog scale (VAS) score for low back pain (VAS-LBP) and leg pain (VAS-LP), Oswestry Disability Index (ODI) and Japanese Orthopaedic Association (JOA) score. Statistical analysis used independent sample t-test and sample t-test. For univariate analysis, the significance was set to p < 0.05. Results: A total of 62 patients undergoing single level MIS-TLIFs between January 2017 and January 2019 were included, with 32 NE-IFC 46.9% female, mean age 54.86±11.65, mean body mass index (BMI) 24.59±3.63) and 30 EXP (40% female, mean age 58.32±12.99, mean BMI 24.45±2.76) with no significant differences in demographics. There were no significant differences between two groups in Operative time (OT), Estimated blood loss (EBL) and Length of stay (LOS). No significant differences were found in VAS-LBP, VAS-LP, JOA and ODI in post-operation and the last follow-up between the two groups. The imaging outcome demonstrated that the mean increase in DH was significantly greater for the EXP-IFC group than for the NE-IFC group at 1 year follow-up (8.92±0.51mm EXP-IFC vs. 7.96±0.96mm NE-IFC, p<0.001). The mean change in FH of operative and contralateral sides were found to be significantly higher for the EXP-IFC group at 1 year follow-up (operative side:17.67±2.29mm EXP-IFC vs. 16.01±2.73mm NE-IFC, p=0.042; contralateral side:17.32±2.26mm EXP-IFC vs. 16.10±2.32mm NE-IFC, p<0.001), but changes in LL and SL were not significantly different. We did not detect any significant difference in fusion rate at the last follow-up between the two groups. Conclusion: Our results indicated that there may be no significant difference in short-term clinical outcomes between EXP-IFC and NE-IFC, but the use of EXP-IFC in MIS-TLIF can provide a significant restoration of disc height, and neural foraminal height compared to NE-IFC.